Activator reloaded - Myofunctional appliance at its best - Anil S Malik; Abhijeet S Karnik (Wolters Kluwer Medknow Publications, 2011)
Orthodontics from time immemorial has always been considered as the first speciality of dentistry. Diagnosis and treatment planning from Dr. Tweed's time always required extraction of four vital and functional premolar teeth. However, many patients, parents and general dentists have failed to understand that orthodontic treatment at an early age can help save the extraction teeth to achieve a full functional and esthetic harmonius dentition. Our case demonstrates a non-extraction orthodontic treatment plan of a developing skeletal Class II malocclusion. The results of this case show a successful correction of Class II molar malocclusion with excellent form and function, which resulted in improvement of the patient's frontal and facial profile, which, thereby boosted her personality and self-confidence.